2021
DOI: 10.7554/elife.65948
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dominance governs the assembly of microbial communities in mixed nutrient environments

Abstract: A major open question in microbial community ecology is whether we can predict how the components of a diet collectively determine the taxonomic composition of microbial communities. Motivated by this challenge, we investigate whether communities assembled in pairs of nutrients can be predicted from those assembled in every single nutrient alone. We find that although the null, naturally additive model generally predicts well the family-level community composition, there exist systematic deviations from the ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 50 publications
2
67
0
Order By: Relevance
“…In contrast, the natural rhizosphere soil environments provide stages for cooperative interaction due to the local presence of diverse nutrients, root exudates, and heterogeneity. These findings are in accordance with previous studies, support the impact of spatial organization and nutrient condition on microbial interaction [ 68 , 69 ]. Our experimental setup involved co-cultivation of B. velezensis and P. stutzeri in liquid medium.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the natural rhizosphere soil environments provide stages for cooperative interaction due to the local presence of diverse nutrients, root exudates, and heterogeneity. These findings are in accordance with previous studies, support the impact of spatial organization and nutrient condition on microbial interaction [ 68 , 69 ]. Our experimental setup involved co-cultivation of B. velezensis and P. stutzeri in liquid medium.…”
Section: Discussionsupporting
confidence: 93%
“…For the microbial growth in in silico experiment, not only resource availability but also resource quality should be considered in the mathematical model. It has been reported that the quality of resources, such as what metabolic by-products are produced from a resource and the combination of resources, influences the assembly of microbial communities [ 39 , 41 ]. For the mathematical model, the phenomenon was reproduced with many parameter sets in this study, but it is also important to identify the parameters of the mathematical model from in situ data by larger field sampling in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns that deviate from the assumption arise from biological phenomena that are deemed non-additive. Much emphasis has been placed on predictions on the additive (or non-additive deviation) nature of growth outcomes in more complex environments (Foster and Bell, 2012;Pacheco et al, 2021;Estrela et al, 2021). Here, we evaluated non-additive responses (e.g.…”
Section: B Thailandensis-p Syringae Interspecies Networkmentioning
confidence: 99%